Drawing Curves of The Rainfall Intensity Duration Frequency (IDF) and Assessment equation Intensity Rainfall for Nasiriyah City, Iraq - Ahmed Awda Dakheel (University of Thi-Qar Journal, 2019)
The rainfall Intensity-Duration-Frequency (IDF) relationship is one of the most commonly used tools in water resources engineering, either for planning, designing and operating of water resource projects. The purpose of this research is to get curves frequency the intensity of rain duration for Nasiriyah city, Iraq, and finding empirical equations the curves. Where are collected data of the rain 36 years ago from 1980 to 2015. Used Indian Meteorological Department (IMD) empirical reduction formula and methods of distribution: Gumbel and Log Pearson Type III during short periods (10, 20, 30, 60,120,180, 360, 720 and1440) minute with a specified return period (2, 5, 10, 25, 50 and 100) years. The results obtained showed that intensity of rainfall decreases with increase in storm duration and rainfall of any given duration will have a larger intensity if its return period is large. The chi-square goodness of fit test was used to determine the best fit methods of distribution (Easy fit software 5.6) and conclude that the Log Pearson type III was the best method.